Game-Based Wordwall in Vocabulary Learning: a Teacher’s Implementation and Students’ Views - Medina, Ravena Ophellia Ditya; Mobit, Mobit; Puspitaloka, Nina (Journal of Educational Sciences, 2024)
The purpose of this research are to investigate the implementation of Game-Based Wordwall in vocabulary learning, then investigate students' perception on the use of Game-Based Wordwall in vocabulary learning. To answer the research questions, the researcher used a qualitative and case study as the research design. This research was carried out in one of the Junior High Schools in Cikampek, West Java. One English teacher and six secondary students participated in this research. The data collection techniques for this research were observation, interview, and documentation. In addition, the instrumentation included the classroom observation checklist, interview guidelines, and lesson plan. After obtaining the data, the researcher processed the data using thematic analysis. The results of this research show that GameBased Wordwall makes the class atmosphere fun. Game-Based Wordwall also found positive perceptions from students, namely during vocabulary learning activities students became active and often answered questions in the game, students felt happy and challenged, then there were many advantages that students received through using Game-Based Wordwall. Therefore, the implementation of Game-Based Wordwall in vocabulary learning is a good strategy because it has many positive perceptions from students.